Q: Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

2(a + 4b)

The expression 18 plus 6 plus 4b simplifies to 24 + 4b.

9a + 3b - 11a - 4b = -2a -b

Related questions

2a + 4b

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

1a+3b 2a+4b=3a +7b

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5

2a*4b*(-3c) = ? 2 * 4 * -3 * a * b * c = ? -24abc

2a-3+4b-2a-b-3+5=3b-1

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

Do this: write it out 2 |2a + 4b + 8 Now what divides into all the numbers? ---------------- a + 2b + 4 answer is 2(a+2b+4)

2(a + 4b)

The expression 18 plus 6 plus 4b simplifies to 24 + 4b.